PSIV-10 The Effect of a Dacitic (rhyolitic) Tuff Breccia, a Hydrated Sodium Calcium Aluminosilicate (HSCAS), Inclusion in Corn-soybean Meal Diets on Growth Performance of Individually Housed Grower Pigs - Chevalier, Tyler B (J Anim Sci, 2021)
Crossbred pigs (24 barrows and 24 gilts; BW 35.59±0.24 kg) were blocked by body weight, sex, and allotted in a randomized complete block design to 3 dietary treatments: 1) Control [CON], 2) CON+0.25%, and 3) CON+0.50% inclusion of a dacitic tuff breccia (DTB) to evaluate effects on growth performance. Diets were formulated to meet or exceed NRC (2012) requirement estimates and fed for 2 phases (d0-14=PHS_1 and d14-28=PHS_2). Diets were limit fed based on metabolic body weight (3.5 x maintenance ME needs [3.5 × 106 Kcal ME/kg BW(0.75)]). Pigs were weighed weekly and feed allowance adjusted accordingly. In PHS_1, a tendency for a sex difference, gilt vs. barrow, respectively, for ADG (4.92%; 0.913 vs. 0.870 kg; P=0.10) and G:F (4.14%; 0.528 vs. 0.507; P=0.06) existed. The responses to treatments 1–3, respectively, for ADG (0.877, 0.900, and 0.896 kg; linear P=0.54) and G:F (0.510, 0.522, 0.521; linear P=0.46) were numerically greater. In PHS_2, sex differences, gilt vs. barrow, respectively, for ADG (5.67%; 0.946 vs. 0.895 kg; P=0.05) and G:F (7.98%; 0.460 vs. 0.426; P< 0.01) existed. The numerical responses to treatments 1–3, respectively, for ADG (0.912, 0.944 and 0.905 kg; P=0.41) and G:F (0.439, 0.446, 0.444; linear P=0.70) continued. A tendency for a quadratic response in ADFI (P=0.06) existed because feed allowance increased with increasing weekly BW for treatments 2 and 3. Overall, sex differences, gilt vs. barrow, respectively, for ADG (5.30%; 0.929 vs. 0.882 kg; P< 0.05) and G:F (6.23%; 0.491 vs. 0.462; P< 0.01) occurred. Numerical responses to treatments 1–3, respectively, for ADG (0.895, 0.921 and 0.900 kg, P=0.32) and G:F (0.471, 0.480, 0.479; linear P=0.50) occurred. Additionally, the response to DTB appeared to be higher in barrows.